Doris Nutall interviewed by Cathy Rummery in the Mark Rummery and Cathy Rummery collection, 1984-1988 - Nutall, Doris, Mrs., 1893-; Rummery, Cathy (1986)
Folkloric recording.
Recorded on 30 June 1986, at St. Lawrence Home for the Aged, Galong, N.S.W.
Digital master available
List of tape contents available (1 p.)
Keywords: Nutall, Doris, -- Mrs., -- 1893- -- Interviews; Folk musicians -- New South Wales -- Galong -- Interviews; Recitations; Folk songs, English -- Australia